Qualitative Analysis of Cancer Pathways with Transition and Place Invariants - Ngandjoug, Guy Romaric Yemeli (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
It is of practical interest to know whether a biological network contains mass-preserving and state-preserving subnetworks. In a mass-preserving subnetwork, the total mass remains constant. In any state-preserving subnetwork, biological reactions bring the subnetwork back to an initial state. For instance, any reversible reaction forms a state-preserving subnetwork. In a large intricate biological network, it is rather cumbersome task to determine mass-preserving and state-preserving subnetworks. P-invariants and T-invariants are analysis methods that can be successfully used to determine mass-preserving and state-preserving subnetworks in a Petri net. In this thesis, the information is derived from the biological databases Reactome and KEGG as well as from the existing literature to date, to create rather detailed Petri net model of cancer pathway, and perform its qualitative analysis with P-invariants and T-invariants. Keywords: Biological network, Petri net, P-invariants, T-invariants.

ÖZ: Bir biyolojik ağın kitle-koruyucu ve durum-koruyucu alt ağlar içerip içermediğini bilmenin pratik önemi vardır. Bir kitle-koruyucu alt ağda, toplam kitle sabittir ve bu nedenle sınırlıdır. Herhangi bir durumu koruyan alt ağda, biyolojik reaksiyonlar alt ağı bu duruma geri getirir. Örneğin, geri-dönüşümlü herhangi bir reaksiyon, durum koruyucu bir alt ağ oluşturur. Büyük ve karmaşık bir biyolojik ağda, kitle ve durum koruyucu alt ağları belirlemek oldukça zorlu bir iştir. P-invariantlar ve T-invariantlar, kitle koruyucu ve durum koruyucu alt ağların belirlenmesinde başarılı olabilen Petri net analiz yöntemleridir. Bu tezde, Reactome ve KEGG gibi biyolojik veri tabanlarından ve mevcut literatürden bilgi derleyerek kanser yollarnın ayrıntılı Petri ağı modeli oluşturulur ve bu modelin P-invariantlar ve T-invariantlar metodları ile nitel analizi yapılmıştır. Anahtar Kelimeler: Biyolojik ağda, Petri net, P-invariantlar, T-invariantlar.
Master of Science in Applied Mathematics and Computer Science. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2019. Supervisor: Prof. Dr. Rza Bashirov.
Keywords: Mathematics; Applied Mathematics and Computer Science; Computational biology; Systems biology; Biological network; Petri net; P-invariants; T-invariants